Visible to NIR Light Photoactivation of Hydrogen Sulfide for Biological Targeting - Štacko, Peter; Muchová, Lucie; Vítek, Libor; Klán, Petr (Organic letters, 2018)
The synthesis and photochemical properties of H2S-releasing BODIPY thiocarbamate photocage scaffolds activatable by visible-to-NIR (up to 700 nm) light to release carbonyl sulfide (COS), which is transformed to H2S using either isolated or natural carbonic anhydrase, is reported. The excellent uncaging cross section and high H2S release yields in in vitro experiments, including live-cell imaging, suggest that these photocages can serve as a platform for the bio-orthogonal phototriggered release within the tissue-transparent window.
Keywords: Biosynthetic Pathways; buněčný tracking; Catalysis; Humans; světlo; Cell Tracking; katalýza; sloučeniny boru; lidé; Optical Imaging; Hep G2 Cells; Light; karboanhydrasy; Hydrogen Sulfide; biosyntetické dráhy; Sulfur Oxides; Thiocarbamates; buňky Hep G2; thiokarbamáty; Boron Compounds; Photochemical Processes; sulfan; oxidy síry; optické zobrazování; Carbonic Anhydrases; fotochemické procesy